The Effectiveness of Bathing and Massage Methods on Stress Levels and Physiological Parameters in Premature Infants in the NICU: A Systematic Review - Suci Rahayu; Allenidekania Allenidekania (GLOBAL HEALTH SCIENCE GROUP, 2026)
Premature infants are at high risk of physiological and neurological disturbances due to organ immaturity. Although bathing is often considered a calming routine, it may act as a significant sensory stressor for premature infants in the neonatal intensive care unit (NICU). This study aimed to evaluate the effectiveness of various bathing methods and complementary interventions in reducing stress levels and maintaining physiological stability in premature infants. A systematic review was conducted following the PRISMA 2020 guidelines. Literature searches were performed across five electronic databases PubMed, Scopus, ScienceDirect, ProQuest, and Sage Journals as well as additional website sources, covering publications from 2016 to 2025. The search used combinations of keywords including premature infant, preterm infant, bathing, stress, physiological stability, and NICU. A total of 634 records were identified, with 50 duplicates removed. After title and abstract screening, 70 full-text articles were assessed for eligibility. Seven randomized controlled trials involving 523 premature infants met the inclusion criteria and were included in the final review. Data were analyzed using narrative synthesis. Swaddled bathing was consistently more effective than conventional bathing methods in maintaining physiological stability and reducing acute stress responses. Complementary interventions, such as aromatherapy massage and mother-led multisensory stimulation, were beneficial as post-bathing strategies to enhance recovery and relaxation. Swaddled bathing is an effective and recommended bathing method for premature infants in the NICU to reduce stress and support physiological stability.